A cognitive stylistics approach to grammar for writing in teacher-student writing conferences - Healey, Brett William (Curtin University, 2024)
In his thesis by publication, Brett synthesised the theory of cognitive stylistics and dialogic pedagogy to construct a situated concept of embodied grammar-for-writing. Through empirical investigation and the application of theory, his work has demonstrated how teachers can scaffold primary students’ authorial processes during writing conferences by focusing on linguistic decisions designed to create narrative imagery that appeals to the reader. His work makes a significant contribution to the pedagogy of writing.